Molasses and Its Additives for Fodder and Green Plants for Ruminant Nutrition - Palani, Zirak M. R.; Ameen, Gulala W.; Shekhani, Dawod Noori M. (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
Molasses, as a by-product of sugar production, is a feed widely used in ruminant diets, which is rich in available sugars and minerals. The present review paper, under this context, evaluates in detail the chemical characterization and nutritional aspects of molasses with an emphasis on it as a rich source of energy, enhancing the feed palatability and encouraging ruminal microbial fermentation. Molasses has been successful in green and conserved forage systems, particularly with improved quality silage and a reduction in feed losses. Feeding molasses with additives such as urea, minerals, and probiotics enhances rumen function, nitrogen utilization efficiency, and fiber digestion. Research has also shown that it has a positive impact on production performance (such as weight gain, higher milk yield, and feed intake). However, limitation still exists with the factors of the risk from sub-acute ruminal acidosis, imbalancing of electrolytes , and variation of animal species and age. Overconsumption leads to ruminal pH and microbial imbalance. It suggests moderate (usually no more than 10% of dry matter) molasses inclusion with the product introduced slowly and balanced with other feed ingredients. It also provides farmers and nutritionists with working tools to realize these advantages without jeopardizing animal health. The need for further research on the activity of molasses in the long term, its interaction with rumen microbiota, and its activity with other additives in sustainable ruminant production systems is emphasised. The future requirements for research into the long-term activity of molasses, its interaction with rumen microbiota, and its activity with other additives in sustainable ruminant production systems is emphasized.